HUBUNGAN USIA IBU BERSALIN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) - Sari, Atika Kurnia; Wahyuni, Sri (MIDWIFERY JOURNAL, 2021)
ABSTRACT : THE RELATIONSHIP BETWEEN  MATERNAL  AGE WITH THE EVENT OF LOW BIRTH WEIGHT (LBW) AT MAYJEND HM RYACUDU KOTABUMI  HOSPITAL, NORTH LAMPUNG Background: According to WHO, the Infant Mortality Rate (IMR) in 2019 was 49 per 1000 live births (WHO, 2019). Pre-survey data at the Mayjend HM Ryacudu Kotabumi Hospital in North Lampung Regency in 2020 found 95 LBW cases from 650 mothers giving birth.Purpose:  is  to  find  out  the  relationship  between  maternal  age  and  the incidence  of  LBW  in  Mayjend  HM  RyacuduKotabumi  Hospital,  North  Lampung Regency in 2020.Methods: is quantitative analytic. The population in this study were all mothers who gave birth at Mayjend HM RyacuduKotabumi Hospital, North Lampung Regency in 2020 as many as 650 mothers gave birth. The sample in this study was a saturated sample of 650 mothers who gave birth. The measuring instrument in this study used a checklist.Results: of this study were obtained from a total sampling of 650 respondents. The results of the chi square test in cases of maternal age at risk with LBW as many as 65 (68.42%), in maternity mothers with a risky age that did not occur LBW as many as 235 (42.34%).Conclusion:The results of statistical tests concluded that there was a relationship between maternal age and the incidence of LBW with the results of X2  count = 22.204 dk = 1, α=0,05 compared to > X2 table 3.841. Value of X2count = 22.204 > X2 table 3.841.Suggestions: Based  on  the  results  of  the  study,  it  is  expected  to  increase  knowledge  for mothers to prepare for a mature reproductive age to undergo pregnancy and the risk of giving birth to LBW. Keywords: Relationship, maternal age, Low Birth Weight     ABSTRAKLatar Belakang : Menurut WHO Angka Kematian Bayi (AKB) pada tahun 2019 ialah sebesar 49 per1000 kelahiran hidup (WHO, 2019). Data prasurvey di RSD Mayjend HM RyacuduKotabumi Kabupaten Lampung Utara Tahun 2020 didapati 95 kasus BBLR dari 650 ibu bersalin.Tujuan: Untuk mengetahui hubungan usia ibu bersalin dengan kejadian BBLR di RSD Mayjend HM Ryacudu Kotabumi Kabupaten Lampung Utara Tahun 2020.Metode: Penelitian ini bersifat analitik kuantitatif. Populasi dalam penelitian ini adalah  seluruh  ibu  bersalin  di  RSD  Mayjend  HM  Ryacudu  Kotabumi  Kabupaten Lampung Utara Tahun 2020 sebanyak 650 ibu bersalin. Sample dalam penelitian ini adalah sample jenuh sebanyak 650 ibu bersalin. Alat ukur dalam penelitian ini menggunakan checklist.Hasil:Penelitian ini diperoleh dari total sampling 650 responden. Hasil  uji chi square pada kasus usia ibu berisiko dengan BBLR sebanyak 65 (10%), pada ibu bersalin dengan usia berisiko yang tidak terjadi BBLR sebanyak 235 (36,15%). Hasil uji statistik disimpulkan bahwa ada hubungan antara usia ibu bersalin dengan kejadian BBLR dengan hasil X2 hitung =  22,204 dk=1, α=0,05 dibandingkan > X2 tabel 3,841. Nilai X2 hitung = 22,204 > X2 tabel 3,841.Kesimpulan: Berdasarkan hasil penelitian, diharapkan meningkatkan pengetahuan bagi para ibu untuk menyiapkan usia reproduksi yang matang untuk menjalani kehamilan dan risiko melahirkan BBLR. Saran Penelitian ini  diharapkan menambah pengetahuan bagi para ibu untuk menyiapkan usia reproduksi yang matang untuk menjalani kehamilan dan resiko melahirkan BBLR  Kata kunci        : Hubungan, Usia ibu, BBLR